Organic evolution - Rastogi, Veer Bala (New Delhi, Medtec, 2014)
It is readable by any undergraduate or graduate student in physics, mathematics, computer science, chemistry or engineering
Glossary 383-394p.; Index 395-405p.
Keywords: Adaptations; Chromosome number; Origin; Variation